The Impact of Metacognitive on the Students' Proficiency in Oral Communication at SMPN 20 Bulukumba - Mallappiang, Yassir; Auliya, Anggi; Maharida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to investigate the impact of metacognitive strategies on students’ fluency in oral communication at SMPN 20 Bulukumba. The study employed a quantitative method with a pre-experimental design, involving class 8A as the sample, consisting of 31 students selected through cluster sampling. The data were collected using a speaking test administered in three stages: pre-test, treatment, and post-test. During the treatment, students were trained to apply metacognitive strategies, including planning, monitoring, and evaluating, to improve their fluency in oral communication. The results revealed that students showed a notable improvement in fluency after the implementation of metacognitive strategies. They became more confident, spoke more smoothly, and reduced hesitation when expressing their ideas. These findings indicate that metacognitive strategies effectively enhance students’ fluency by promoting greater awareness and control over their speaking performance.